2015
DOI: 10.5942/jawwa.2015.107.0023
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Manganese Removal in a Pilot‐Scale Postfiltration Contactor

Abstract: A model of manganese (Mn) adsorption and subsequent oxidation by chlorine was applied to experimental data from two pilot‐scale postfiltration Mn contactors to estimate the oxidation rate constant. Experiments showed the ability of the contactors to adequately remove soluble Mn under varying operating conditions. A pseudo first‐order rate expression was found to be more appropriate than a second‐order rate expression. The fitted, pseudo first‐order rate constant ranged from 2.8 × 10–4 to 5.2 × 10–4/s and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Thus, we conclude that the dependence of kC on chlorine concentration was small, confirming our prediction that k and kC would be independent of chlorine concentration when equation ( 5) was derived from equations ( 2) to (4). Bierlein et al (2015) and Knocke et al (2010) have reported similar results for the effect of free chlorine concentration on the removal of Mn(II) by MnOx. Li et al (2019a) have also reported no change in the Mn(II) removal rate at chlorine doses of 1 to 4 mg/L.…”
Section: Removal Rate Coefficient and Its Independence From Mn(ii) An...mentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, we conclude that the dependence of kC on chlorine concentration was small, confirming our prediction that k and kC would be independent of chlorine concentration when equation ( 5) was derived from equations ( 2) to (4). Bierlein et al (2015) and Knocke et al (2010) have reported similar results for the effect of free chlorine concentration on the removal of Mn(II) by MnOx. Li et al (2019a) have also reported no change in the Mn(II) removal rate at chlorine doses of 1 to 4 mg/L.…”
Section: Removal Rate Coefficient and Its Independence From Mn(ii) An...mentioning
confidence: 55%
“…Li et al (2019a) have interpreted the pseudo-first-order reaction kinetics of Mn(II) removal from the perspective of chemical oxidation. However, we applied an external-film mass transfer model because this model has been widely used to describe Mn(II) removal by MnOx-coated filter media in the presence of chlorine in previous studies (Bierlein et al, 2015;Dashtban Kenari et al, 2019;Merkle et al, 1997). These studies present the model equations in the form of removal kinetics using filter media, but the basic form of the reaction kinetics can be written as follows:…”
Section: Removal Rate Coefficient and Its Independence From Mn(ii) An...mentioning
confidence: 99%
“…The two-resistance model incorporating mass-transfer and oxidation rates has been applied in previous studies analyzing Mn 2+ removal with a granular MnO X catalyst ( Bierlein et al., 2015 ; Kenari et al., 2019 ; Merkle et al., 1997 ). MnO X would have a higher adsorption capacity for Mn 2+ than activated carbon, which reduces the rate resistance of adsorption, and the particle size of MnO X , which is much larger than SPAC/PAC, increases the mass-transfer resistance.…”
Section: Resultsmentioning
confidence: 99%
“…They assumed the local equilibrium of the Freundlich adsorption isotherm in the Mn 2+ adsorption process. The basics of the Merkle model have been followed in later studies ( Bierlein et al., 2015 ; Kenari et al., 2019 ). …”
Section: Introductionmentioning
confidence: 99%
“…In traditional groundwater treatment systems based on aeration followed by rapid filtration with no chemical dosage, manganese removal is possible due to the presence of manganese dioxide catalyst on the grains of the filtration material [3][4][5]. The chemically non-active filtration material, such as silica sand, has to be activated first by covering the grains with manganese dioxide during the filtration of natural groundwater [6]. After activation of filtration material, manganese removal becomes an autocatalytic and heterogenic process [2,5].…”
Section: Introductionmentioning
confidence: 99%